1992
DOI: 10.1029/92jb00041
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic tomography and acoustic emission in hydraulically fractured Lac du Bonnet Grey granite

Abstract: Ultrasonic tomography and acoustic emission (AE) data were obtained during laboratory hydraulic fracturing tests on two large, unconfined cylinders of Lac du Bonnet grey granite. The cylinders were internally pressurized over four to five cycles prior to final failure. Compressional velocities were measured before and after each pressurization cycle with an array of 16 evenly spaced transducers around the central, cross-sectional plane of each sample. Sixteen channels of whole waveform AE data were recorded du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 22 publications
2
37
0
1
Order By: Relevance
“…In rock mechanics a survey of the literature shows that not much work has been reported on imaging of cracks by the ultrasonic method. However, references are available on ultrasonic imaging of microcrack development in granitic rocks based on ultrasonic velocity measurements (Janson et Falls et al 1992;Young 1993). The advantages of the C-scan imaging method are (Nagaraja Rao et al 1995) as follows: (i) the size, shape, and orientation of the defective region can be mapped in a plan view; (ii) except for cutting, grinding, and polishing, laborious sample preparation is not required; (iii) the interior of a sample can be examined in a nondestructive manner; (iv) a large section of the sample can be examined, and it is possible to study how the crack distribution varies from location to location; and (v) the method is less time consuming.…”
Section: Ultrasonic C-scan Imaging Of Microcrack Damagementioning
confidence: 99%
“…In rock mechanics a survey of the literature shows that not much work has been reported on imaging of cracks by the ultrasonic method. However, references are available on ultrasonic imaging of microcrack development in granitic rocks based on ultrasonic velocity measurements (Janson et Falls et al 1992;Young 1993). The advantages of the C-scan imaging method are (Nagaraja Rao et al 1995) as follows: (i) the size, shape, and orientation of the defective region can be mapped in a plan view; (ii) except for cutting, grinding, and polishing, laborious sample preparation is not required; (iii) the interior of a sample can be examined in a nondestructive manner; (iv) a large section of the sample can be examined, and it is possible to study how the crack distribution varies from location to location; and (v) the method is less time consuming.…”
Section: Ultrasonic C-scan Imaging Of Microcrack Damagementioning
confidence: 99%
“…In an experiment where water pressure was employed to generate fractures in granite, Falls et al (1992) found that the directions with lower UWTR were vertical to the direction paralleling the microfractures. The experiment from Matsuoka (1984) proved that UWTR apparently increased after blocks were immersed in water.…”
Section: Ultrasonic Wave Transmitting Rate Changesmentioning
confidence: 99%
“…Such induced microseismicity can be used as a diagnostic tool to define the geometry and nature of failure of the individual events, regardless of HF scale (e.g., Ishida, 2001;Falls et al, 1992;Majer and Doe, 1986;Lockner and Byerlee, 1977). For this reason, microseismic monitoring is routinely used for monitoring stimulations of EGS reservoirs (Niitsuma et al, 1999) and more recently in oil and gas fracturing operations (e.g., Caffagni et al, 2016;Warpinski et al, 2013;Maxwell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%